2005
DOI: 10.1242/dev.01711
|View full text |Cite
|
Sign up to set email alerts
|

The zinc finger transcriptional repressor Blimp1/Prdm1 is dispensable for early axis formation but is required for specification of primordial germ cells in the mouse

Abstract: Blimp1, a zinc-finger containing DNA-binding transcriptional repressor,functions as a master regulator of B cell terminal differentiation. Considerable evidence suggests that Blimp1 is required for the establishment of anteroposterior axis formation and the formation of head structures during early vertebrate development. In mouse embryos, Blimp1 is strongly expressed in axial mesendoderm, the tissue known to provide anterior patterning signals during gastrulation. Here, we describe for the first time the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
326
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(351 citation statements)
references
References 52 publications
19
326
1
3
Order By: Relevance
“…They arise as a small subset of cells, in the extraembryonic mesoderm (ExM), at around 7.25 dpc identified by high levels of alkaline phosphatase (APase) activity [11]. The transcriptional regulator Blimp1 (B-lymphocyte-induced maturation protein-1, also known as Prdm1) has been identified as a key factor for the specification of PGCs [12,13]. Gene expression profiling has shown that founder PGCs are characterized by high levels of an interferon-inducible transmembrane protein, fragilis/mil-1/ifitm3 and exclusive expression of a small nuclear Author contributions: S.D.…”
Section: Introductionmentioning
confidence: 99%
“…They arise as a small subset of cells, in the extraembryonic mesoderm (ExM), at around 7.25 dpc identified by high levels of alkaline phosphatase (APase) activity [11]. The transcriptional regulator Blimp1 (B-lymphocyte-induced maturation protein-1, also known as Prdm1) has been identified as a key factor for the specification of PGCs [12,13]. Gene expression profiling has shown that founder PGCs are characterized by high levels of an interferon-inducible transmembrane protein, fragilis/mil-1/ifitm3 and exclusive expression of a small nuclear Author contributions: S.D.…”
Section: Introductionmentioning
confidence: 99%
“…Except of functions in immune-related cells, Prdm1 plays key roles in the development of a wide variety of tissues in mice [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In mice, Prdm1 is expressed in endoderm, mesoderm and ectoderm-derived tissues during embryonic development [37].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, Prdm1 is expressed in endoderm, mesoderm and ectoderm-derived tissues during embryonic development [37]. Prdm1 governs germ cell specification [23][24][25] and regulates development of the sebaceous gland [26], skin epidermis [27], the posterior forelimb, caudal pharyngeal arches, sensory vibrissae, heart [28], photoreceptor [29], and intestine [30,31]. Prdm1 also is a tumor suppressor in blood cells [32][33][34][35] by regulating P53 expression [36].…”
Section: Introductionmentioning
confidence: 99%
“…2A) and express both pluripotency and early germline markers. In particular, the nascent PGCs are characterised by the expression of Prdm1 , Prdm14 and Tfap2c (or Ap2γ ), transcription factors required for PGC specification at E7.25 37, 38, 39. Both Prdm1 and Prdm14 seem to be under the direct regulation of the Bmp‐Smad pathway 39 and also under the regulation of the classic mesendodermal marker Brachyury (or T), upregulated by Bmps from the extra‐embryonic regions 40.…”
Section: Pgc Specification In Mouse: the Paradigm For Mammalsmentioning
confidence: 99%